Interpopulational differences in the nutritional condition of Aequiyoldia eightsii (Protobranchia: Nuculanidae) from the Western Antarctic Peninsula during austral summer - Bascur, Miguel; Morley, Simon A.; Meredith, Michael; Muñoz Ramírez, Carlos P.; Barnes, David K. A.; Schloss, Irene Ruth; Sands, Chester J.; Schofield, Oscar; Román Gonzaléz, Alejandro; Cárdenas, Leyla; Venables, Hugh; Brante, Antonio; et al. (PeerJ)
The Western Antarctic Peninsula (WAP) is a hotspot for environmental change and has a strong environmental gradient from North to South. Here, for the first time we used adult individuals of the bivalve Aequiyoldia eightsii to evaluate large-scale spatial variation in the biochemical composition (measured as lipid, protein and fatty acids) and energy content, as a proxy for nutritional condition, of three populations along the WAP: O'Higgins Research Station in the north (63.3°S), Yelcho Research Station in mid-WAP (64.9°S) and Rothera Research Station further south (67.6°S). The results reveal significantly higher quantities of lipids (L), proteins (P), energy (E) and total fatty acids (FA) in the northern population (O'Higgins) (L: 8.33 ± 1.32%; P: 22.34 ± 3.16%; E: 171.53 ± 17.70 Joules; FA: 16.33 ± 0.98 mg g) than in the mid-WAP population (Yelcho) (L: 6.23 ± 0.84%; P: 18.63 ± 1.17%; E: 136.67 ± 7.08 Joules; FA: 10.93 ± 0.63 mg g) and southern population (Rothera) (L: 4.60 ± 0.51%; P: 13.11 ± 0.98%; E: 98.37 ± 5.67 Joules; FA: 7.58 ± 0.48 mg g). We hypothesize these differences in the nutritional condition could be related to a number of biological and environmental characteristics. Our results can be interpreted as a consequence of differences in phenology at each location; differences in somatic and gametogenic growth rhythms. Contrasting environmental conditions throughout the WAP such as seawater temperature, quantity and quality of food from both planktonic and sediment sources, likely have an effect on the metabolism and nutritional intake of this species. Fil: Bascur, Miguel. Universidad Catolica de la Santisima Concepcion.; Chile Fil: Morley, Simon A. British Antarctic Survey; Reino Unido Fil: Meredith, Michael. British Antarctic Survey; Reino Unido Fil: Muñoz Ramírez, Carlos P. Universidad Catolica de la Santisima Concepcion.; Chile Fil: Barnes, David K. A. British Antarctic Survey; Reino Unido Fil: Schloss, Irene Ruth. Universidad Nacional de Tierra del Fuego; Argentina. Consejo ...